A extrafiscalidade como mecanismo de preservação ambiental: refil PET 100% reciclável - Abrosio, Claudia Cristina dos Santos (2021)
This work aims to analyze Brazilian taxes as a governmental instrument to implement policies of environmental protection, which is an established right by the Brazilian Constitution of 1988. In summary, the study will comprise the analysis of the Constitutional Tax System as well as its guidelines, targeting an outcome which allows to reconcile tax regulation with environment preservation. Some aspects of the environmental issues in Brazil will be evaluated, as well as the state of inertia in fostering enough means to protect the environment – in order to either repair it or diminish its damages –, with the view of providing the current and future generations with life quality. The study focuses on the evaluation of how taxes can induce certain behaviors, showing that their use can lead to strengthening environmental and social values. This work also spotlights the increasing use of plastic packaging by society – from the production to disposal phases – as a reflection of the current fast time we live in. In this scenario, 100%- recycled pet refillable bottles appear as one of the possible alternatives in the search for sustainable development. For this purpose, we will try to pinpoint some models of tax incentives from a legal entity’s perspective, in order to address the need of an effective environmental policy, encouraging, at once, the production as well the consumption of completely recycled refillable pet bottles. In other words, this study will analyze how tax stimulus would lead private agents into adopting socially responsible practices, which might not occur without them